2022
DOI: 10.7554/elife.72707
|View full text |Cite
|
Sign up to set email alerts
|

Cellular organization in lab-evolved and extant multicellular species obeys a maximum entropy law

Abstract: The prevalence of multicellular organisms is due in part to their ability to form complex structures. How cells pack in these structures is a fundamental biophysical issue, underlying their functional properties. However, much remains unknown about how cell packing geometries arise, and how they are affected by random noise during growth - especially absent developmental programs. Here, we quantify the statistics of cellular neighborhoods of two different multicellular eukaryotes: lab-evolved ‘snowflake’ yeast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 84 publications
1
38
0
Order By: Relevance
“…Indeed, similar 3D patterns of rough growth have been observed in other living systems, namely in multicellular clusters of Saccharomyces cerevisiae, usually referred to as 'snowflake yeast clusters', or in aggregation clusters of the green alga Volvox carteri. Recent research has shown that the sizes and morphologies of these clusters are crucially determined by growth and crowdinginduced mechanical stresses coupled to environment conditions [143][144][145][146][147]. These works have suggested the tantalizing idea that the morphological adaptation of large 3D clusters to environmental constraints could provide insight into the origins of multicellularity.…”
Section: Substrate Concentration Cinmentioning
confidence: 99%
“…Indeed, similar 3D patterns of rough growth have been observed in other living systems, namely in multicellular clusters of Saccharomyces cerevisiae, usually referred to as 'snowflake yeast clusters', or in aggregation clusters of the green alga Volvox carteri. Recent research has shown that the sizes and morphologies of these clusters are crucially determined by growth and crowdinginduced mechanical stresses coupled to environment conditions [143][144][145][146][147]. These works have suggested the tantalizing idea that the morphological adaptation of large 3D clusters to environmental constraints could provide insight into the origins of multicellularity.…”
Section: Substrate Concentration Cinmentioning
confidence: 99%
“…However, the inherent stochasticity of the cell division process, combined with any curvature of the tissue, makes it unlikely that crystalline arrangements of cells will prevail across the entire organism. 18 In experimental images of select cases, we indeed see that the intercellular bond network has a disorder (see, e.g., Refs. 18 and 73 and Fig.…”
Section: Permanent Intercellular Bondsmentioning
confidence: 65%
“… 18 In experimental images of select cases, we indeed see that the intercellular bond network has a disorder (see, e.g., Refs. 18 and 73 and Fig. 3 ).…”
Section: Permanent Intercellular Bondsmentioning
confidence: 65%
See 2 more Smart Citations